ApoE ε4 Is Associated With Cognition, Brain Integrity, and Atrophy in HIV Over Age 60. (1st December 2016) - Wendelken, Lauren A.; Jahanshad, Neda; Rosen, Howard J.; Busovaca, Edgar; Allen, Isabel; Coppola, Giovanni; Adams, Collin; Rankin, Katherine P.; Milanini, Benedetta; Clifford, Katherine; Wojta, Kevin; Nir, Talia M.; et al.
Abstract : Background: There are contradicting reports on the associations between Apolipoprotein E4 (ApoE ε4) and brain outcomes in HIV with some evidence that relationships may be greatest in older age groups. Methods: We assessed cognition in 76 clinically stable HIV-infected participants over age 60 and genotyped ApoE. Sixty-one of these subjects underwent structural brain magnetic resonance imaging and diffusion tensor imaging. Results: The median age of the participants was 64 years (range: 60–84) and the median estimated duration of HIV infection was 22 years. Apo ε4 carriers (n = 19) were similar to noncarriers (n = 57) in sex (95% vs. 96% male), and education (16.0 vs. 16.2 years) ApoE ε4 carriers demonstrated greater deficits in cognitive performance in the executive domain ( P = 0.045) and had reduced fractional anisotropy and increased mean diffusivity throughout large white matter tracts within the brain compared with noncarriers. Tensor-based morphometry analyses revealed ventricular expansion and atrophy in the posterior corpus callosum, thalamus, and brainstem among HIV-infected ApoE ε4 carriers compared with ε4 noncarriers. Conclusions: In this sample of older HIV-infected individuals, having at least 1 ApoE ε4 allele was associated with decreased cognitive performance in the executive functioning domain, reduced brain white matter integrity, and brain atrophy. Brain atrophy was most prominent in the posterior corpus callosum, thalamus, and brainstem. This pattern of cognitive deficit, atrophy, and damage to white matter integrity was similar to that described in HIV, suggesting an exacerbation of HIV-related pathology; although emergence of other age-associated neurodegenerative disorders cannot be excluded. Abstract : Supplemental Digital Content is Available in the Text.